Ferramenta AcheSeuEcoponto: auxiliando a população e o gestor público na destinação adequada dos resíduos sólidos. - Melaré, Angelina Vitorino de Souza (2014)
The population growth combined with the industrial development and the increasing consumption caused several problems related to the solid waste management such as inadequate disposal. Due to global pressures and new polices such as the Solid Waste National Policy, managers need to find solutions to reduce, reuse and recycle waste. The Information and Communication Technologies and the Geographic Information Systems are worldwide used in solutions for waste management. Some of these proposals show that the appropriate disposal increases due to the proximity between the population and the disposal points. This thesis presents a computational tool, called AcheSeuEcoponto, which seeks to assist the population to properly allocate their solid residues. This tool was developed using Geo and Web technologies in a fourth-module architecture. The tool offers to citizens querying the nearest disposal point and disposal points by type of residue . Also, AcheseuEcoponto provides map visualization of the disposal points and directions from a starting point to a disposal point. The social network module allows us to disseminate the tool and as a consequence the disposal points. In addition, the tool provides to managers strategic reports related to poor areas of disposal points, the most popular points and the public profile. As part of this work, we answered questions that measure the scope of the tool, the influence of Web technologies on the dissemination of tool, and the public profile including their knowledge about disposal points. For this purpose, data were collected and analyzed using a questionnaire filled out via the tool, and a Web analytics service. Some results were expected, but the percentage of people who showed lack of knowledge of disposal points was beyond expectation, highlighting the importance of researches within the context of solid waste management.